Mechanisms of improved nitrogen utilization and root architecture in cotton under reduced fertilization: a comparative study of individual and group planting systems - Wang, Sijia; Zhao, Jinghua; Wang, Chunxia; Yang, Tingrui (Frontiers in Agronomy, 2025)
IntroductionExcessive nitrogen application poses a multifaceted challenge to modern intensive agriculture, causing adverse effects including soil acidification, groundwater contamination and greenhouse gas emissions. These environmental consequences threaten the sustainability of global agricultural systems and impair cotton growth performance and resource-use efficiency. Under China’s national policy of zero-growth in fertilizer application, it is critical to elucidate the spatial distribution patterns of cotton root systems under nitrogen reduction conditions, quantify the contributions of water and nitrogen inputs to total nitrogen accumulation in different cotton organs, and analyze water-nitrogen management interactions to enhance water and nitrogen use efficiency in cotton cropping systems.MethodsIn this study, three irrigation quotas (488 mm, 444 mm, and 400 mm are denoted as W1, W2, and W3) and four nitrogen fertilization levels (440 kg ha–1, 387 kg ha–1, 336 kg ha–1, and 294 kg ha–1, respectively) were implemented in 2023 through root box and field experiments to investigate root growth dynamics and nitrogen accumulation in cotton fields. Water-nitrogen interactions significantly affected cotton root morphology.ResultsThe mean root diameter in the 15–50 cm soil layer exhibited strong responsiveness to irrigation, with optimal growth observed under the W3N3 treatment (400 mm irrigation and 336 kg ha-1 nitrogen). Under W1 irrigation (488 mm), root length density (RLD) and diameter showed minimal differences between N1 and N2 treatments, whereas root surface area density (RSAD) of the N4 treatment demonstrated significant irrigation-dependent variation. Total nitrogen content across cotton organs followed the order: leaves > stems > roots, showing positive correlation with nitrogen application rate. The irrigation quota (48.0%–51.3%) was found to contribute more to plant nitrogen content than nitrogen application (22.7%–48.7%). Nitrogen application was identified as the primary contributor to soil total nitrogen accumulation in all soil layers within the limited-area study; however, in the open-field experiment, it was observed to contribute most significantly (27.4%) to soil total nitrogen accumulation specifically in the 0-40 cm soil layer.DiscussionThis study provides theoretical and technical support for optimizing cotton production, enhancing water-nitrogen use efficiency, and promoting environmental sustainability in Xinjiang’s arid farming systems.